FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG SEKTOR PROPERTY, REAL ESTATE DAN BUILDING CONSTRUCTION - Prasetyo, Ekky Rowy; Beny, Beny (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The focus of this research was to identify the independent variable on debt policy of the several variables examined, including profitability, liquidity, asset structure, dividend policy, and sales growth. The companies in the property, real estate, and building construction sectors that are listed on the Indonesia Stock Exchange from 2013 to 2020 are the study objects. Purposive sampling was applied as the sample technique, yielding 56 total data from 7 companies. According to the research’s findings, profitability and asset structure don’t have influence on debt policy, however liquidity has a negative effect on debt policy. Meanwhile, the debt policy and sales growth have a positive influence on debtpolicy